Biomaterials as implants in the orthopedic field for regenerative medicine: metal versus synthetic polymers - Al-Shalawi, Faisal Dakhelallah; Mohamed Ariff, Azmah Hanim; Jung, Dong-Won; Mohd Ariffin, Mohd Khairol Anuar; Seng Kim, Collin Looi; Brabazon, Dermot; Al-Osaimi, Maha Obaid (Multidisciplinary Digital Publishing Institute, 2023)
Patients suffering bone fractures in different parts of the body require implants that will enable similar function to that of the natural bone that they are replacing. Joint diseases (rheumatoid arthritis and osteoarthritis) also require surgical intervention with implants such as hip and knee joint replacement. Biomaterial implants are utilized to fix fractures or replace parts of the body. For the majority of these implant cases, either metal or polymer biomaterials are chosen in order to have a similar functional capacity to the original bone material. The biomaterials that are employed most often for implants of bone fracture are metals such as stainless steel and titanium, and polymers such as polyethene and polyetheretherketone (PEEK). This review compared metallic and synthetic polymer implant biomaterials that can be employed to secure load-bearing bone fractures due to their ability to withstand the mechanical stresses and strains of the body, with a focus on their classification, properties, and application.